The biological applications of exosomal-based materials in bone/cartilage tissue engineering - Chen, Ruiqin; Cheng, Yanan; Zhang, Wentao; Zhang, Hongbiao; Yuan, Xiaoli (Frontiers in Materials, 2023)
Exosomes are secreted by various cells including stem cells, dendritic cells, and tumor cells, also known as the cell-derived extracellular vesicles. Exosomes, can carry informative cargos from host cells, thus have been employed as potential nanomaterials for their multifarious biological functions in biomedical fields, such as drug and genes delivery, tumor targeting, and disease treatment. Recently, the biological applications of exosomes in bone tissue engineering have gained increasing attention. Some important progress has been made while the tissue regeneration and functional recovery of boneremain as the key challenges to be addressed. In this article, we first made a summary of exosomes and their applications in the regeneration of bone and cartilage tissue. Then, modification approaches used for exosomes to equip them with excellent capacities are summarized. Finally, current concerns and future outlooks of exosomes in bone/cartilage tissue engineering and regeneration are discussed.